Islamic Microeconomics and Financial Inclusion: A Study of Waqf in Community Economic Empowerment - Hidayati, Siti Nur; Mahsun, Mahsun; Kusumawati, Ratna Dewi; Salihin, Agus; Ridho, Muhammad Zainul (Ekonomi Syariah IAIN Kudus, 2025)
This research explores the role of waqf as a social and economic development instrument in Islamic finance, focusing on its contributions to poverty reduction, empowerment of minorities and women, and financial inclusion. The researcher gathered, evaluated, and synthesized relevant literature sources on the study subject through a literature review. Academic resources, including Google Scholar, Springer, ScienceDirect, and Scopus, were utilized to search for the works, which comprised journal articles, books, reports, theses, and policy papers. The review entails identifying the primary themes present in the literature, while also critically assessing the study methods, findings, and generalizability. This study utilizes literature reviews and secondary data analysis to illuminate the role of waqf in supporting disadvantaged communities by funding small businesses, partnering with individuals experiencing poverty to access healthcare and education, and other initiatives. In addition, it highlights the challenges associated with waqf implementation, including issues with donor administration, a lack of transparency, and inefficiency. Additionally, the study examines the broader economic and social aspects of waqf, including its potential to generate revenue and promote communal development. Research reveals substantial barriers to the effectiveness of waqf, including bureaucratic delays and underfunding, despite its potential role in social welfare. Therefore, the results highlight the importance of waqf-based programs requiring improved accountability, governance, and sustainability. Despite waqf's potential to alleviate poverty and strengthen communities, the research finds that these obstacles must be removed before the solution can have any lasting effect.